Trapped - Tagwira, Valerie (Weaver Press, 2020)
Trapped explores the lives of three characters: Unesu is a doctor, Cashleen trained as a journalist and Delta qualified as a chemical engineer. Unesu is employed, but his work exposes him to the deficiencies in the system every day as he faces the challenges of life and death. Each of the two young women, good friends, daunted by having their job applications repeatedly rejected, make moral and ethical compromises in order to find work, or at least an income that will pay their bills. These three individuals provide the pivot around which the action unfolds, introducing the reader to people and situations that paint a vital picture of life in Harare at a time of crisis, when survival depends on courage, determination, friendship and humour.